Transcript host-RNA signatures to discriminate bacterial and viral infections in febrile children - Buonsenso, Danilo; Sodero, Giorgio; Valentini, Piero (Pediatric research, 2022)
Traditional laboratory markers, such as white blood cell count, C-reactive protein, and procalcitonin, failed to discriminate viral and bacterial infections in children. The lack of an accurate diagnostic test has a negative impact on child's care, limiting the ability of early diagnosis and appropriate management of children. This, on the one hand, may lead to delayed recognition of sepsis and severe bacterial infections, which still represent the leading causes of child morbidity and mortality. On the other hand, this may lead to overuse of empiric antibiotic therapies, particularly for specific subgroups of patients, such as infants younger than 90 days of life or neutropenic patients. This approach has an adverse effect on costs, antibiotic resistance, and pediatric microbiota. Transcript host-RNA signatures are a new tool used to differentiate viral from bacterial infections by analyzing the transcriptional biosignatures of RNA in host leukocytes. In this systematic review, we evaluate the efficacy and the possible application of this new diagnostic method in febrile children, along with challenges in its implementation. Our review support the growing evidence that the application of these new tools can improve the characterization of the spectrum of bacterial and viral infections and optimize the use of antibiotics in children. IMPACT: Transcript host RNA signatures may allow to better characterize the spectrum of viral, bacterial, and inflammatory illnesses in febrile children and can be used with traditional diagnostic methods to determine if and when to start antibiotic therapy. This is the first review on the use of transcript RNA signatures in febrile children to distinguish viral from bacterial infections. Our review identified a wide variability of target populations and gold standards used to define sepsis and SBIs, limiting the generalization of our findings.